India as Known to the Ancient World - Banerjee, Gauranganath (Brill | Manohar Publishers & Distributors, 2024)
During ancient times, many civilizations such as Egypt, China, Mesopotamia, Europe and others flourished. This created a sense of interaction based on culture, economy, crafts, and language. India too was part of this said experience. India as Known to the Ancient World discusses how India became a center of attraction for its civilizational value. The prime focus of this book is to assess the role and contribution of India during the antiquarian age in other parts of the world such as Egypt, Central Asia, Europe, the Middle East, China, and South East Asia.